PERAN STRUKTUR KEPEMILIKAN DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN MANUFAKTUR - Cornelius, Ekky; Rahayuningsih, Deasy Ariyanti (E-Jurnal Akuntansi TSM, 2023)
This study aims to provide empirical evidence on the ownership structure and factors that affect the firm value in manufacturing companies. . The independent variables used in this study are profitability, leverage, liquidity, firm size, capital structure, institutional ownership managerial ownership, company growth and total asset turnover (TATO). The dependent variable of this study is the company value. This study used population data from manufacturing companies that are consecutively listed on the Indonesian Stock Exchange (IDX) during the period of 2019-2021. This study used the purposive sampling method to select data samples, resulting in 31 manufacturing companies that met the criteria. This study used multiple regression method to test the hypotheses of the influence of independent variables on the dependent variable. The results of the study showed that profitability, institutional ownership and managerial ownership have a positive influence on firm value, while other variables such as leverage, liquidity, firm size, capital structure, company growth and total asset turnover (TATO) do not have a significant impact on firm value.